INVESTIGATING STUDENTS’ PROBLEMS IN LISTENING COMPREHENSION OF TOEFL LIKE –TEST AT STKIP PGRI SUMATERA BARAT ACADEMIC YEARS 2018/2019 - Ade Putra; Elmiati Elmiati (Sean Institute, 2023)
Based on the research question above, the purpose of this research is to investigate students’ problems in listening comprehension of TOEFL like –test at STKIP PGRI Sumatera Barat academic years 2018/2019. Sample researcher will get 20 students who could be sample of this research. As a result of this research, the researcher found the answer for the researcher question that had been previously. The researcher found that the students’ problems in listening comprehension are pronounciations, cultural value, sentence complexity, speed rate delivery, colloquial, and mishearing. The finding were all of the respondents had problems in similar sound, students have problems with clarity of speaker sound, almost all of students have problem because unfamiliar with different accent, the sound unclear and chunk the connected sound make her confused, sentence listened by listener chunk the connected sound and make her difficult to understand speaker said, and she did not understand cultural value of the native speaker, she difficult to know meaning of the speaker said..